THE FORMULATION OF LEARNING STEPS THROUGH THE AL-ISLAH WA AT-TAGYR METHOD IN REALIZING INDIVIDUAL PIETY - Nurti Budiyanti; Muhamad Parhan; Mohammad Rindu Fajar Islamy (Universitas Pendidikan Indonesia, 2022)
The morality of students in the era of modernity has been reduced so sharply. The phenomenon of juvenile delinquency is mushrooming, unbridled promiscuity, ethics that are far from the customs of manners, weak speech, lack of discipline and work ethic are of little concern to Muslim intellectuals to solve the problematic. It is necessary to formulate the right learning steps, in order to provide alternative solutions in directing student activities in a more positive direction. This study aims to formulate learning steps through the Method of Al-Ishlah Wa At-Tagyir by Sholeh Sulthan, in order to realize individual diversity. By using a qualitative approach and literature review method. The results of this study show that the formulation of learning steps through the Al-Ishlah Wa At-Tagyir method is divided into two stages, namely the pre-instructional stage and the instructional stage. The pre-instructional stage includes sky management, positive paradigms, earth management and gradual learning. While the instructional stage includes providing motivation, observation- analysis- solutive, learning with optimal effort, and prevention. The formulation of learning steps through the Method of Al-Ishlah Wa At-Tagyir is directed towards achieving better individual serendipity.